The identity of open space: adapting from the model of traditional neighborhood center - Ahmadi .I; Che-Ani .A.I; Farckisch .H; Surat .M (Penerbit UKM, 2011)
The City form consists of some different elements, which have been joined in the functional and spatial form. If these elements have an appropriate spatial organization the strong coherence is created among them. In the traditional urban spaces, most of the times, this spatial regularity among city elements is the result of thoughtful developed urban patterns. Many non-local agents influence on the form of new cities while the forming of traditional urban spaces depends on the morphology of the site, the historical background and the culture of local people. In this way, we were looking for some of the important researches by focus the open